From Trenches to the Crest, effectuating a Greater Beneficence of Terminology Development to National Language Policy: the Nigeria Case - C. I. C, Cardinal, (Universitas PGRI Madiun, 2024)
Terminology development as a tool that propels the evolvement of educational and translation materials and services besides enhancing the formation of a robust terminology is widely celebrated as a great linguistic tool. This is because of its’ potency in knitting together a multilingual society like Nigeria towards a common understanding and purpose. The afore-stated promotion of national unity, effective communication and the preservation of indigenous languages directed towards the creation of an inclusive nation are the same goals pursued by the National Policy on Education which couches Nigeria’s Language Policy. Consequently, this study titled, ‘From Trenches to the Crest, effectuatinga Greater Beneficence of Terminology Development to National Language Policy: The Nigeria Case’, primarily aims to explore the meritorious services of terminology development in the evolution, realization and implementation of an effective language policy in Nigeria. By surveying the historical development of Nigeria language policy, it identifies and condemns the overemphasis of the usage of English language for instructional and legislative purposes, pointing out its disservices to indigenous languages. The study also highlights the fundamental roles and challenges impeding a fuller beneficence of a symbiosis of terminology development and the National Language Policy in achieving national integration. Adopting the hermeneutical and content analysis methods of enquiry, the research in conclusion, suggests a novel pragmatic and proactive terminology development model, which will drive a vibrant language policy and implementation.